2003
DOI: 10.1007/s00595-003-2612-5
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer with Endocrine Differentiation: Report of Two Cases Showing Different Histologic Patterns

Abstract: We report two cases of breast cancer with endocrine differentiation. Case 1 was a 56-year-old woman with a 2-cm tumor in the upper outer quadrant of the right breast and right axillary lymphadenopathy. Excisional biopsy suggested carcinoma and we performed breast-conserving surgery with lymph node dissection. Histologic examination revealed breast cancer with endocrine differentiation resembling small cell carcinoma of the lung, with one nodal metastasis. Case 2 was a 71-year-old woman with a 2.5-cm tumor in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…1,6 However, some investigators have reported poor prognosis in patients with primary neuroendocrine carcinomas. 9,11 In our case, extensive regional metastases and additional studies of the metastatic lesions in the pancreas and liver excluded other primary tumors, supporting the diagnosis of a primary breast lesion. Retrospective histological and immunohistochemical examination of the initial breast lesion confirmed its neuroendocrine nature.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…1,6 However, some investigators have reported poor prognosis in patients with primary neuroendocrine carcinomas. 9,11 In our case, extensive regional metastases and additional studies of the metastatic lesions in the pancreas and liver excluded other primary tumors, supporting the diagnosis of a primary breast lesion. Retrospective histological and immunohistochemical examination of the initial breast lesion confirmed its neuroendocrine nature.…”
Section: Discussionsupporting
confidence: 64%
“…8 Its histogenesis is unclear but it is thought to arise from endocrine differentiation of a breast carcinoma rather than preexisting endocrine cells in the breast. 9,10 Neuroendocrine tumors of the breast are usually seen in elderly patients, with an age range between the sixth and seventh decades. 8,10,11,12,13 The prognosis of primary, early stage, neuroendocrine carcinoma of the breast compares favorably with other breast carcinomas with the histologic grade being one of the most important predictors of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Primary breast small cell carcinoma is extremely rare, and absence of other non-mammary primary sites as well as the presence of in situ component will be required before establishing this diagnosis (Sridhar et al, 2004). Breast small cell carcinoma, being classified as tumors with endocrine differentiation, is the rarest, but the highest, grade of malignancy with prominent vascular invasion and nodal metastasis (Ajisaka et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…PrimaryNEC of the breast is thought to arise from endocrine differentiation of a breast carcinoma rather than from pre-existing endocrine cells in the breast (3). Focal neuroendocrine differentiation can be found in different histological types of breast cancers, however the term neuroendocrine carcinoma is applied when more than 50% of the neoplastic cells express neuroendocrine markers (chromogranin A, synaptophysin andneuron-specific enolase)(4).…”
Section: Definitionmentioning
confidence: 99%